Development Of Wifi 6 Based Computer Network At LPK Sulthoon 4M - Ananda, Rizky; Alamsyah, Hendri; Mardiana, Yessi (Jurnal Media Computer Science, 2025)
The development of computer networks has reached various aspects of life, with its wide use by groups and individuals. Computer network technology is very important because it has many advantages, such as developing a Wi-Fi 6-based computer network at LPK Sulthoon 4M to improve network performance and overcome the obstacles of slow connections that often occur when many devices are connected. The research method used is a field research approach with the stages of observation, interviews, documentation, and network quality testing. The network development process was conducted through the Network Development Life Cycle (NDLC) method, which includes requirements analysis, topology design, Wi-Fi 6 device implementation, and network performance testing based on Quality of Service (QoS) parameters, such as throughput, delay, jitter, and packet loss. The test results show a significant increase in data transfer speed with an average throughput of 5,049.71 kbps and a packet loss rate of 0%, and an average delay of 6.55 ms. The implementation of Wi-Fi 6 is proven effective in improving network stability and speed, thus supporting the smooth running of digital-based learning activities at LPK Sulthoon 4M.